Comparison of the growth of two Arabidopsis thaliana ecotypes and tranformation efficiency in UPM’s transgenic house - Mis Man, Khairul Anuar (2015)
Arabidopsis thaliana is a small flowering plant in the mustard family (Brassicaceae). It is used to study the genetic improvement of plants and is a model organism in agricultural biotechnology. Therefore, the identification of suitable varieties for genetic experiments including the Columbia (Col-O) ecotype and Landsberg (Ler-0) ecotype is important. The objective of this experiment is to compare the growth rate of Columbia (Col-O) and Landsberg (Ler-0) A. thaliana ecotypes and the transformation efficiency in UPM's Transgenic Green House. The parameters used to measure the growth rate were size of leaf and height of plant. The Columbia (Col-O) and Landsberg (Ler-0) took around eight weeks two finish the life cycle. The Columbia (Col-O) has been reported to have very robust growth and average growth characteristic compared to Landsberg (Ler-0) which has shorter stems and smaller siliques. It is expected that the two ecotypes will also vary in the growth rate and transformation efficiency when grown in the UPM’s Transgenic Greenhouse. Agrobacterium tumefaciens strain LBA4404 that harbour the binary vector pMDC32 will mediate transformation of A. thaliana which was performed on the Columbia (Col-0) ecotypes and the transformation efficiency was compared subsequently after culturing on regeneration medium with containing hygromycin at 60 mg/litre. The transformation was successfully where the percentages seeds germinated on MS media are 56.67% with the addition of the antibiotic.